Savings bonds, retractable bonds and callable bonds - Brennan, Michael J.; Schwartz, Eduardo S. (Journal of Financial Economics, 1977)
Savings bonds, retractable bonds and callable bonds are each equivalent to a straight bond with an option. Neglecting default risk the value of these contingent claims depends upon the riskless interest rate. This paper employs the option pricing framework to value these bonds, under the assumptions that the interest rate follows a Gauss-Wiener process and that the pure expectations hypothesis holds.